ANALISIS PENGARUH KAPASITAS INDUSTRI, PEMBERDAYAAN DAN TEKNOLOGI TERHADAP PRODUKTIVITAS SERTA KESEJAHTERAAN PELAKU USAHA INDUSTRI KAIN TENUN IKAT DI KABUPATEN KLUNGKUNG - Antara, Gede Eka Dharma; Utama, Made Suyana; Marhaeni, A.A I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The problem faced by IKM business operators including business productivity issues and welfare tended to decrease in Klungkung regency. This study have purpose to: 1) analyze the development of weaving industrial enterprises, 2) to analyze the effect of industry capacity and empowerment on the productivity, 3) to analyze the effect of industry capacity, empowerment and productivity of the welfare, 4) analyzing technology's role in moderating the effect of industrial capacity and empowerment on the productivity, 5) Analyze the role of productivity in mediating the effect of industry capacity and empowerment of the welfare. This research was conducted at weaving industrial sites Klungkung regency. The number of samples taken as many as 50 businesses weaving using saturation sampling. Data analysis technique used is the Partial Least Square (PLS). The results of this study are 1) The development of the weaving industry in the Klungkung regency decreased in 2010 until 2016. 2) There is positive and significant effect industrial capacity and empowerment to productivity 3) There is a positive and significant effect industrial capacity, empowerment and productivity of the welfare, 4) Technology does not moderate the effect of the relationship industrial capacity and empowerment to productivity, 5) Productivity mediates the effect of industry capacity and empowerment in the welfare.
Keywords: IKM, industry capacity, Empowerment, Technology, Productivity, Welfare